Patent Compulsory Licensing System on China’s Road to Clean Energy Technology: A Solution or Pointless Decoration for Energy Innovation? - Bofan Zhang (Law and Economy, 2023)
Along with the increasing global climate change and ecological damage, energy transformation driven by clean energy technology is an important guarantee to cope with climate change and promote the high-quality and efficient development of a country’s economy. Under the principle of common but differentiated country under the Kyoto Protocol, more and more developing countries call for the implementation of a compulsory licensing system for clean energy technology, and the compulsory licensing of patents for clean energy technology refers to the compulsory licensing of patents by the patent administration of a country grants a patent license directly to a third party without the consent of the patentee under specific circumstances and in accordance with the statutory conditions. This paper examines the historical development and current situation of the patent compulsory licensing system for clean energy technologies, studies the implementation of the system and the evolution of the legal system in the United States, reflects on the current situation of China’s patent compulsory licensing system and the possibility of extending the licensing content to clean energy technologies, and proposes policies and laws and regulations to solve the corresponding problems, in order to explore the future of China’s patent compulsory licensing system for clean energy technologies. The proposed policy and legal proposals aim to explore the conditions for establishing a future Chinese patent compulsory licensing system for clean energy technologies and its practical contribution to China’s energy transition and carbon neutrality and carbon peaking.